Effectiveness in Switching from Antipsychotic Polypharmacy to Monotherapy in Patients with Schizophrenia: A Case Series - Kamei, Hiroyuki (Clin Psychopharmacol Neurosci, 2020)
In Japan, drug therapy for schizophrenia is characterized by high-dose antipsychotic polypharmacy, which is an uncommon approach internationally. In this study, we reduced the number of antipsychotic agents in 5 patients using the Safety Correction of High-dose Antipsychotic Polypharmacy (SCAP) method and conducted a survey regarding treatment satisfaction. The switch from polypharmacy to monotherapy was achieved in all patients. There was no deterioration in psychiatric symptoms, and adverse reactions were reduced. Three of the subjects were satisfied with the decrease in the number of antipsychotic agents and dose-reduction. These results suggest that the SCAP method is a safe and useful method that can be applied in a clinical setting.